Mental Health Literacy and Mental Help-Seeking Intention among Female Healthcare Workers: A Cross-Sectional Study - Faizah, Nur; Paskarini, Indriati; Rahayu, Sri (Journal of Educational, Health and Community Psychology, 2025)
Mental health literacy is regarded as a significant factor influencing an individual's intention to seek professional psychological help when confronted with mental health issues. The elevated psychosocial risks inherent to the profession of healthcare work render these individuals particularly susceptible to mental health issues, with a higher prevalence observed among females. This study aims to assess the relationship between mental health literacy and mental help-seeking intention among female healthcare workers, and to explore potential associations between sociodemographic characteristics and these variables. Methods: A total of 140 female healthcare workers were surveyed. The data collection instrument included socio-demographic characteristics, Mental Health Literacy (MHL), and Mental Help-Seeking Intention Scale (MHSIS) questionnaire. Data were analyzed using Kruskal-Wallis, Pearson correlation, simple and multiple linear regression. The results showed that mental health literacy showed a significant positive correlation with mental help-seeking intention (r = 0.395, p < 0.001). Simple linear regression indicated MHL significantly predicted help-seeking intention (β = 0.395, p < 0.001). Multiple linear regression controlling for age, tenure, and marital status confirmed MHL remained a significant predictor (β = 0.375, p < 0.001). However, Kruskal-Wallis tests found no significant differences in variables by socio-demographic factors (p > 0.05). The findings highlight the importance of mental health literacy in influencing an individual’s intention to seek professional help. Although socio-demographic factors showed no significant effect, mental health literacy remains a key factor in addressing mental health issues among female healthcare workers.